English proficiency among college students using language learning software to enhance their productive skills - Telen, Jay D. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2016)
The study described the relationship between the English proficiency of college students using the DynEd courseware and the productive skills among college students of Jose Rizal Memorial State University, Dapitan City. Using the Slovin’s formula and simple proportionate stratified sampling with lottery method, there were 184 respondents out of the 340 college students of Jose Rizal Memorial State University Main Campus, Dapitan City who were officially enrolled in the JEEP-Start I and II for the 1st and 2nd semesters, SY 2011-2012. The DynEd records manager was used to find out the placement test levels of the respondents in the entry and exit placement tests in JEEP-Start I and JEEP-Start II. The researchers used a customized questionnaire with essay topics for a composition writing to test the writing skills of the respondents and speech topics for an extemporaneous speaking to test the speaking skills. The study found out that the respondents were skillful in their productive skills in English language as exhibited in their writing and speaking tests results. However, their entry and exit placement tests performance in the JEEP Start-I and II indicated that the students were not proficient in the English language. The students’ English proficiency using the DynEd Courseware was positively correlated to their productive skills level in both speaking and writing, hence, students’ productive skills depend on their language proficiency.